Advancements in Immunotherapy for Oral Cancer Research - Zeng, Tianyi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Oral cancer is one of the common malignant tumors of the head and neck. The survival rate in the late stage is about 50%. At present, more and more immunotherapy is gradually used in the clinical treatment of oral cancer. Some relevant experiments on the efficacy of immunotherapy for the treatment of oral cancer are also actively carried out. However, at present, there is a lack of the latest experimental data on the review of immunotherapy for oral cancer, and the classification method is quite single. This paper divides oral cancer into three stages: prevention, early and late stages, and comprehensively evaluates and analyzes the application effects of immunotherapy at each stage. In particular, based on the KEYNOTE-048 trial data in February 2023, it elaborates on the therapeutic effect of Pembrolizumab in patients with advanced oral cancer. Although there are many types of immunotherapy, some are still only in the theoretical stage and have limited clinical data in oral cancer. At the same time, the treatment boundaries for different stages are still unclear, and clinical applications mainly depend on the patient's immune status and condition. This review aims to provide more valuable reference for further research.